Crosslinked HPPE copolymers for foam applications
The shortcomings of existing EVA copolymer foam materials in these aspects are solved by using copolymers of ethylene and alkyl (meth)acrylates and ethylene and vinyl acetate, combined with foam composition additives.
Patent Information
- Application Number
- CN202380052033.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-13
- Filing Date
- 2023-07-12
- Publication Date
- 2025-03-18
AI Technical Summary
The existing EVA copolymer foam materials have shortcomings in terms of mechanical properties and temperature stability, especially in terms of impact absorption, performance consistency under temperature changes and the realization of low foam density.
Foam compositions containing copolymers of ethylene and alkyl (meth)acrylate and copolymers of ethylene and vinyl acetate are prepared by foaming and crosslinking processes using foaming and improving mechanical properties and temperature stability.
The improved mechanical properties of foam materials and performance consistency over a wide temperature range are achieved, the demand for foaming agents is reduced, and the stability of foam materials to temperature changes is improved.
Smart Images

Figure BDA0005229367220000121 
Figure BDA0005229367220000131 
Figure BDA0005229367220000132
Abstract
Description
Technical Field
[0001] The present invention relates to a foam composition comprising a copolymer of ethylene and an alkyl (meth)acrylate and optionally a copolymer of ethylene and vinyl acetate. The present invention also relates to a foam material obtainable from the foam composition, to a method for preparing an article comprising the foam material, and to a footwear article comprising the foam material. Background Art
[0002] Foam products of cross-linked high pressure polyethylene (HPPE) copolymers for various applications, such as sports and leisure, packaging, building and construction, transport, W&C, tapes and medical services, are usually based on monomers of fossil origin. The most commonly used HPPE copolymer is a copolymer of ethylene and vinyl acetate (EVA).
[0003] The use of EVA copolymer as the main polymer component of foamed products is beneficial because of its low production cost and mature process methods. In addition, it is characterized by good adhesion to various substrates, which is often required in foam applications.
[0004] However, EVA copolymers have some disadvantages. For example, some mechanical properties, such as impact absorption (as reflected by the deceleration and force peak of the foam), are compromised, which are important for many target applications, especially footwear applications. In addition, EVA copolymers often show inconsistent performance to temperature changes, that is, if used at different temperatures (e.g., 23°C vs. -20°C), the performance of solid and expanded products will be completely different.
[0005] Furthermore, EVA copolymers are characterized by a limited foaming capacity. Therefore, in order to achieve sufficiently low foam densities, a large amount of blowing agent must be added to the formulation, and for some EVA copolymers, low foam densities are even impossible to achieve.
[0006] Decomposition and acid generation are another disadvantage in the preparation of EVA copolymers when manufactured at moderate to elevated processing temperatures, especially at longer processing times associated with crosslinked and foamed products.
[0007] To minimize the main problems or limitations in the performance of foamed EVA copolymers, other polymers such as olefin block copolymers (OBC), thermoplastic polyurethanes (TPU) or styrene-ethylene-butylene-styrene (SEBS) are added to EVA copolymers in large quantities. These are usually highly engineered polymers that are usually much more expensive and therefore not suitable for low-priced foams.
[0008] For example, U.S. Patent Application No. US2019 / 0276650 A1 discloses a foam composition and its use in footwear articles, wherein the foam composition comprises an EVA copolymer and a composite block copolymer.
[0009] Therefore, a new foam material is needed to overcome the above-mentioned shortcomings. Summary of the invention
[0010] It is an object of the present invention to provide novel foam materials which feature improved mechanical properties and / or which exhibit more consistent mechanical properties over a wide temperature range.
[0011] Therefore, the present invention provides a foam composition comprising:
[0012] a) a resin composition comprising:
[0013] a1) 25 to 100 phr of a copolymer of ethylene and an alkyl (meth)acrylate, wherein the alkyl (meth)acrylate is selected from methyl (meth)acrylate and butyl (meth)acrylate; and
[0014] a2) 0 to 75 phr of a copolymer of ethylene and vinyl acetate; and
[0015] b) 1 to 25 phr of foam composition additives.
[0016] The present invention also provides a method for manufacturing an article, the method comprising:
[0017] A) mixing a foam composition comprising:
[0018] a) a resin composition comprising:
[0019] a1) 25 to 100 phr of a copolymer of ethylene and an alkyl (meth)acrylate, wherein the alkyl (meth)acrylate is selected from methyl (meth)acrylate and butyl (meth)acrylate; and
[0020] a2) 0 to 75 phr of copolymers of ethylene and vinyl acetate;
[0021] b) 1 to 25 phr of a foam composition additive;
[0022] B) molding and curing the foam material in a mold; and
[0023] C) removing the foamed material from the mold and producing an article comprising or consisting of the foamed material.
[0024] Furthermore, the present invention provides a foam material obtainable from the foam composition, provides a footwear article comprising or consisting of the foam material, and provides the use of the foam material in an article for improving the stability of the article to temperature changes. DETAILED DESCRIPTION
[0025] Foam composition
[0026] The foam composition of the present invention comprises a resin composition and a foam composition additive. The foam composition is a non-crosslinked and non-foamed foam composition, which can be obtained by foaming and crosslinking, preferably, by using a chemical foaming agent and a peroxide to obtain a foam material.
[0027] Resin composition
[0028] The resin composition comprises 25 to 100 phr of a copolymer of ethylene and an alkyl (meth)acrylate, wherein the alkyl (meth)acrylate is selected from methyl (meth)acrylate and butyl (meth)acrylate.
[0029] The term "alkyl (meth)acrylate" includes both "alkyl methacrylate" and "alkyl acrylate", wherein alkyl acrylate is a preferred alkyl (meth)acrylate.
[0030] Similarly, the term "methyl (meth)acrylate" (M(M)A) includes both "methyl methacrylate" and "methyl acrylate", and the term "(methyl)butyl acrylate" (B(M)A) includes both "butyl acrylate" and "butyl acrylate", among which methyl acrylate (MA) and / or butyl acrylate (BA) are preferred alkyl (meth)acrylates.
[0031] The copolymers EM(M)A and EB(M)A include EMMA and EMA, or EBMA and EBA, respectively.
[0032] In one embodiment, the resin composition consists only of a copolymer of ethylene and methyl (meth)acrylate (EM(M)A) or butyl (meth)acrylate (EB(M)B). In another embodiment, the resin composition comprises 25 to 75 phr, for example, 25 to 35 phr or 65 to 75 phr, of EM(M)A copolymer or EB(M)A copolymer. Preferably, the resin composition comprises an EB(M)A copolymer.
[0033] The term "phr" stands for parts per hundred of resin and generally refers to the weight content of a compound based on the weight of the resin, wherein the weight of the resin (usually the matrix polymer) is considered to be 100%. For example, 10 phr of compound A means that 10 kg of compound A is added to 100 kg of resin.
[0034] EM(M)A and EB(M)A copolymers are well known and are usually produced by high pressure free radical processes, such as tubular processes or autoclave processes. For example, they are commercially available from companies such as Dow Chemical Company, ExxonMobil Corporation, Westlake Chemical Company, Repsol Corporation and Borealis Chemical Company.
[0035] In the EB(M)A copolymer, butyl (meth)acrylate may be n-butyl (meth)acrylate or isobutyl (meth)acrylate, or a combination of the two. The EM(M)A and EB(M)A copolymers comprise ethylene monomer and methyl (meth)acrylate comonomer or butyl (meth)acrylate comonomer, or consist of ethylene monomer and methyl (meth)acrylate comonomer or butyl (meth)acrylate comonomer. They are preferably free of other comonomers. The content of the (meth)acrylate comonomer is preferably 10 wt.% to 45 wt.%, more preferably 15 wt.% to 35 wt.%, and most preferably 17 wt.% to 30 wt.%, based on the total weight of the respective EM(M)A or EB(M)B copolymer. The comonomer content is typically determined by NMR spectroscopy, as described herein. The copolymer may contain additives for its preparation or for optimizing its characteristics.
[0036] The EM(M)A copolymer preferably has an MFR2 in the range of 1.0 g / 10 min to 4.0 g / 10 min, more preferably in the range of 1.5 g / 10 min to 2.5 g / 10 min. The EB(M)A copolymer preferably has an MFR2 in the range of 2.0 g / 10 min to 5.0 g / 10 min, more preferably in the range of 3.0 g / 10 min to 4.0 g / 10 min. MFR2 is typically determined according to ISO 1133 at a load of 2.16 kg and a temperature of 190°C.
[0037] The EM(M)A copolymer preferably has a 3 Up to 960kg / m 3 range, more preferably 940kg / m 3 Up to 955kg / m 3 The EB(M)A copolymer preferably has a density of 915 kg / m 3 Up to 935kg / m 3 range, more preferably 920kg / m 3Up to 930kg / m 3 Density is usually determined according to ISO 1183.
[0038] The EM(M)A and EB(M)A copolymers preferably have a crystallization temperature (Tc) in the range of 65° C. to 80° C., more preferably in the range of 70° C. to 75° C., and / or have a melting temperature (Tm) in the range of 85° C. to 100° C., more preferably in the range of 90° C. to 95° C. The crystallization temperature and the melting temperature can be determined by the DCS method according to ISO 11357-3.
[0039] The resin combination can also include the copolymer of ethylene and vinyl acetate (EVA) of the amount of up to 75phr. In one embodiment, the resin combination does not include any EVA copolymer. In another embodiment, the resin combination includes 25phr to 75phr, for example, includes 25phr to 35phr or 65phr to 75phr of EVA copolymer.
[0040] EVA copolymers are well known and are generally produced as described above for EM(M)A and EB(M)A copolymers. They are commercially available from companies such as ExxonMobil, Repsol and The Dow Chemical Company.
[0041] The EVA copolymer comprises ethylene monomer and vinyl acetate comonomer, or is composed of ethylene monomer and vinyl acetate comonomer. They preferably do not contain other comonomers. The content of vinyl acetate comonomer preferably accounts for 10wt.% to 90wt.%, more preferably 15wt.% to 50wt.%, and most preferably 20wt.% to 40wt.% of the total weight of the EVA copolymer. In the EVA copolymer, the relative content of vinyl acetate and ethylene can affect polymer properties. Higher vinyl acetate content can make polymers softer and more flexible, while lower vinyl acetate content can make polymers harder and more crystalline. Comonomer content is usually measured by NMR spectroscopy, as described herein. The copolymer can include additives for its preparation or for optimizing its characteristics.
[0042] The EVA copolymer preferably has an MFR2 in the range of 2.0 to 4.0 g / 10 min, more preferably in the range of 1.5 to 2.5 g / 10 min, the MFR2 being determined according to ISO 1133 at a load of 2.16 kg and a temperature of 190°C.
[0043] The EVA copolymer preferably has a strength of 935 kg / m 3 Up to 960kg / m 3 range, more preferably 945kg / m3 Up to 957kg / m 3 The density is within the range, the density being determined according to ISO 1183.
[0044] The EVA copolymer preferably has a crystallization temperature (Tc) in the range of 45°C to 60°C, more preferably in the range of 50°C to 55°C, and / or has a melting temperature (Tm) in the range of 70°C to 80°C, more preferably in the range of 72°C to 77°C, as determined by the DCS method according to ISO 11357-3.
[0045] A particularly preferred resin composition comprises 25 to 35 phr of an EVA copolymer and 65 to 75 phr of an EB(M)A or EM(M)A copolymer (preferably an EB(M)A copolymer); or comprises 65 to 75 phr of an EVA copolymer and 25 to 35 phr of an EB(M)A or EM(M)A copolymer (preferably an EB(M)A copolymer).
[0046] Foam composition additives
[0047] The foam composition comprises from 1 phr to 25 phr of a foam composition additive.
[0048] Preferably, the foam composition comprises the resin composition and at least one of a blowing agent and a cross-linking agent.
[0049] Preferably, the foam composition comprises a chemical foaming agent, which may be present in an amount of 0.1 to 10 phr, more preferably 0.1 to 3 phr. The chemical foaming agent is a thermally decomposable type (generally in the temperature range of 120°C to 200°C) and is selected from organic chemical foaming agents and inorganic chemical foaming agents. Examples of foaming agents include azodicarbonamide, 2,2'-azobisisobutyronitrile, azohexahydrobenzonitrile, azodiaminobenzene and other azo compounds; benzenesulfonylhydrazine, benzene-1,3-sulfonylhydrazine, diphenylsulfone-3,3'-disulfonylhydrazine, diphenoxy-4,4'-disulfonylhydrazine, 4,4'-oxybis(benzenesulfonylhydrazine), p-toluenesulfonylhydrazine and other sulfonylhydrazine compounds; terephthaloylhydrazine, p-tert-butylbenzoylhydrazine and other azide compounds; and sodium bicarbonate, ammonium bicarbonate, ammonium carbonate and other carbonate compounds. Azodicarbonamide (ADCA) is the preferred chemical blowing agent in the present invention because of its satisfactory performance / cost ratio. Additionally or alternatively, physical blowing agents such as halogenated hydrocarbons, volatile organic compounds or non-flammable inert atmosphere gases may also be used.
[0050] It has been found that the resin composition of the present invention requires a lower concentration of blowing agent to achieve similar low foam density compared to pure EVA copolymer. In a specific embodiment, the chemical blowing agent is present in an amount of 0.1 phr to 2 phr, even in an amount of 0.1 phr to 1.5 phr.
[0051] In addition, the foam composition preferably includes a foaming agent activator, which may be present in an amount of 0.1 phr to 10 phr, more preferably 0.1 phr to 3 phr. The foaming agent activator is used to reduce the decomposition temperature of the foaming agent. Foaming agent activators include metal oxides and metal salts as well as organic metal complexes and other compounds. Examples of foaming agent activators are zinc oxide, zinc stearate, zinc nitrate, zinc phthalate, zinc carbonate, tribasic zinc sulfate, magnesium oxide and other inorganic salts and oxides; fatty acid zinc soaps, fatty acid lead soaps, fatty acid cadmium soaps and other metal soaps; boric acid, oxalic acid, succinic acid, adipic acid and other acids; urea, ethanolamine, glucose and glycerol; and combinations thereof. Zinc oxide (ZnO) is a preferred foaming agent activator in the present invention.
[0052] Preferably, the foam composition comprises a crosslinking agent, which may be present in an amount of 0.1 phr to 3 phr, more preferably 0.1 phr to 1.5 phr. The crosslinking agent is preferably an organic peroxide. Under the temperature conditions of the reaction, the peroxide is activated and the crosslinking process begins by extracting hydrogen atoms from the polymer backbone, thereby providing sites for crosslinking. Crosslinking the foam in this way during the foaming process will result in the foamed article having improved physical properties. The nature and concentration of the peroxide crosslinking agent are selected so as to provide suitable foaming and crosslinking in combination with the blowing agent. Examples of organic peroxides are diisopropylbenzene peroxide, tert-butyl isopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3,4,4-di(tert-butylperoxy)valerate n-butyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butyl peroxybenzoate and 1,3-bis(tert-butylperoxyisopropyl)benzene, and combinations thereof, wherein 1,3-bis(tert-butylperoxyisopropyl)benzene (BIBP) is a preferred crosslinking agent in the present invention. Additionally or alternatively, crosslinking can be performed by irradiation.
[0053] Examples of other additives that may be used optionally include thixotropic agents such as chalk, lime and silica particles; lubricants; surfactants; acid scavengers; nucleating agents such as calcium carbonate, silica, talc or lime; processing aids such as waxes; antioxidants; UV stabilizers; dyes and pigments such as titanium dioxide; adhesion promoters; fillers such as talc, silica, magnesium carbonate, magnesium silicate, calcium carbonate, clay, mica, barium sulfate and magnesium hydroxide; bactericides and flame retardants. Typically, the amount of these additives in the foam composition is 0 to 20 phr, preferably 0 to 15 phr.
[0054] In one embodiment, the foam composition comprises one or more of the additives b1) to b4):
[0055] b1) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a chemical blowing agent;
[0056] b2) 0.1 to 3 phr, preferably 0.1 to 1.5 phr, of a crosslinking agent;
[0057] b3) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a blowing agent activator; and
[0058] b4) 0 to 20 phr, preferably 0 to 15 phr, of other foam composition additives.
[0059] Preferably, the foam composition comprises at least additives b1) to b3).
[0060] In one embodiment, the foam composition comprises, preferably consists of:
[0061] a) a resin composition comprising, preferably consisting of:
[0062] a1) 25 to 100 phr of a copolymer of ethylene and an alkyl (meth)acrylate, wherein the alkyl (meth)acrylate is selected from methyl (meth)acrylate and butyl (meth)acrylate; and
[0063] a2) 0 to 75 phr of a copolymer of ethylene and vinyl acetate; and
[0064] b1) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a chemical blowing agent;
[0065] b2) 0.1 to 3 phr, preferably 0.1 to 1.5 phr, of a crosslinking agent;
[0066] b3) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a blowing agent activator; and
[0067] b4) 0 to 20 phr, preferably 0 to 15 phr, of other foam composition additives.
[0068] In another embodiment, the foam composition comprises, preferably consists of:
[0069] a) a resin composition comprising, preferably consisting of:
[0070] a1) 25 to 100 phr of a copolymer of ethylene and butyl (meth)acrylate; and
[0071] a2) 0 to 75 phr of a copolymer of ethylene and vinyl acetate; and
[0072] b1) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a chemical blowing agent;
[0073] b2) 0.1 to 3 phr, preferably 0.1 to 1.5 phr, of a crosslinking agent;
[0074] b3) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a blowing agent activator; and
[0075] b4) 0 to 20 phr, preferably 0.1 to 15 phr, of other foam composition additives.
[0076] In another embodiment, the foam composition comprises, preferably consists of:
[0077] a) a resin composition comprising, preferably consisting of:
[0078] a1) 25 to 75 phr of a copolymer of ethylene and butyl (meth)acrylate; and
[0079] a2) 25 to 75 phr of a copolymer of ethylene and vinyl acetate; and
[0080] b1) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a chemical blowing agent;
[0081] b2) 0.1 to 3 phr, preferably 0.1 to 1.5 phr, of a crosslinking agent;
[0082] b3) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a blowing agent activator; and
[0083] b4) 0 to 20 phr, preferably 0 to 15 phr, of other foam composition additives.
[0084] In another embodiment, the foam composition comprises the resin composition and the foam composition additive described in the above preferred embodiment, and preferably consists of the resin composition and the foam composition additive described in the above preferred embodiment.
[0085] Foam material
[0086] The foam material of the present invention can be obtained by foaming and crosslinking a foam composition, preferably by using a foaming agent and a crosslinking agent. The foam material is preferably a crosslinked foam material produced from a non-crosslinked, non-foamed foam composition.
[0087] The foam material of the present invention refers to a solid polymer material containing gas-filled areas. Solid foams can be closed-cell or open-cell. In closed-cell foams, the gas forms discrete bubble cells (pockets), each of which is completely surrounded by solid material. In open-cell foams, the bubble cells are interconnected.
[0088] The foam material of the present invention is preferably a closed-cell foam material, in which the cell cells filled with a gas, in particular air, are enclosed by a solid matrix of polymer material.
[0089] Depending on the content of the blowing agent, different densities can be adjusted. The density of the foam material of the present invention is preferably between 0.10 g / cm 3 Up to 0.50g / cm 3 In the range of 0.14 g / cm 3 Up to 0.35g / cm 3 In the range of 0.16 g / cm 3 Up to 0.30g / cm 3 and most preferably 0.16 g / cm 3 To 0.28g / cm 3 The range is as follows.
[0090] In a specific embodiment, the density of the foam material of the present invention is 0.20 g / cm 3 Up to 0.28g / cm 3 In the range of . As determined by the DTMA method, the embodiments with the respective densities show a further improved stability to temperature changes. This applies in particular to compositions comprising mixed EVA / EM(M)A and EVA / EB(M)A copolymers as well as pure EB(M)A copolymers.
[0091] The content of crosslinked foam is determined by the xylene heat insoluble (XHU) fraction. The XHU fraction in the foam of the invention is preferably in the range of 85 to 95 wt.%, preferably in the range of 88 to 94 wt.%, based on the total weight of the foam, determined according to ISO 10147.
[0092] Preferably, the foam material is characterized by at least one of the following features:
[0093] c1) Storage modulus E' measured at -20°C -20 Storage modulus E' measured at 23 °C 23 The ratio of is less than 65, preferably in the range of 1 to 65, wherein the storage modulus is measured by dynamic mechanical thermal analysis (DMTA) as described below;
[0094] c2) Volume loss due to wear is less than 1500mm 3 , preferably 300mm 3 Up to 1500mm 3 wherein the volume loss is determined as described below; and
[0095] c3) a shrinkage of less than 5%, preferably in the range of 1% to 5%, based on the average length in the machine direction injection molding and the transverse direction, wherein the shrinkage is determined as described below.
[0096] Preferably, the foam material is characterized by two of the characteristics c1, c2 and c3, more preferably by all three of the characteristics c1, c2 and c3.
[0097] In a specific embodiment, the foam material is characterized by a storage modulus E' measured at -20°C. -20 Storage modulus E' measured at 23 °C 23 The ratio of is less than 40, preferably less than 28, and more preferably in the range of 5 to less than 28; and / or the volume loss caused by wear is less than 1000mm 3 , preferably 500mm 3 To less than 1000mm 3 In another specific embodiment, the foam material is characterized by a shrinkage value of less than 2.5%.
[0098] Excellent stability to temperature changes allows the foam to maintain consistent stiffness and performance in different seasons. This property is particularly advantageous in footwear applications because it allows similar performance shoes to be used in summer and winter.
[0099] The foam material preferably has a foam hardness in the range of 35 to 65, more preferably in the range of 40 to 63, as measured as described below.
[0100] The foam material preferably has a peak deceleration in the range of 20G to 26G, more preferably in the range of 22G to 25G, wherein G is 9.81 m / s 2 , measured as described below at a force peak of up to 2.0 kN (preferably in the range of 1.5 kN to 2.0 kN).
[0101] The deceleration and peak force values are related to the impact absorption of the foam. Lower peak deceleration and peak force values give the foam better impact absorption and impact energy distribution. This is particularly beneficial in footwear applications.
[0102] The foam material preferably has a tear strength in the machine direction, measured according to ISO 20875, in the range of 15 to 100 N / cm, more preferably in the range of 25 to 95 N / cm.
[0103] Higher tear strength provides better bond strength. If the foam material is used as, for example, a midsole of a shoe, higher tear strength results in better resistance to delamination and maintains good bond strength between the foam material in the midsole and outsole and the fabric portion of the shoe.
[0104] Foam materials are also characterized by desirable properties such as high elasticity, low compression set and other mechanical properties, particularly those necessary for good footwear performance.
[0105] Preparation of foam materials
[0106] The foam material of the present invention is prepared from a foam composition, preferably by using a chemical blowing agent and a peroxide crosslinking agent. The foam material is a crosslinked foam material produced from the non-crosslinked non-foamed foam composition of the present invention, and the foam material comprises a resin composition and a foam composition additive.
[0107] The foam material can be produced by different processes, such as compression molding, injection molding, and mixing of extrusion and molding. The process can include mixing / blending a resin composition (comprising one or more polymers) and an additive to obtain a uniform foam composition. If the resin composition includes more than one polymer, the polymer can be pre-mixed (e.g., melt-mixed) before mixing with the additive, or can be in contact with each other when mixed with the additive. Standard equipment can be used for mixing / blending, by adjusting conditions such as time, temperature, shear rate, etc., to achieve good dispersion without premature crosslinking or foaming. Exemplary mixing temperatures are in the range of 80° C. to 150° C.
[0108] After mixing and optional shaping (e.g., forming into sheets by sheet rollers or forming into pellets by extruders), the mixture can be filled into a mold (e.g., a compression mold) and foamed by exposure to a higher temperature, which is generally in the range of 120° C. to 200° C., depending on the type of blowing agent and optional blowing agent activator. The higher temperature condition also activates the crosslinking agent, which reacts with the polymer to form a three-dimensional network.
[0109] The foam materials of the invention thus formed are suitable for conventional fields of foam application, for example as insulating, sealing or damping material, for example for sound damping or heat damping, or as molded articles, for example as cushioning material for furniture or mattresses, and preferably as or in footwear articles.
[0110] Footwear
[0111] The present invention also relates to an article of footwear, comprising or consisting of a foam material according to any of the above embodiments.
[0112] In particular, the excellent consistency of properties over a wide temperature range (eg, as measured by DMTA at -20°C and 23°C) makes the foam materials of the present invention very suitable for use as or in articles of footwear.
[0113] The article of footwear may be a shoe or a portion thereof selected from the group consisting of a sole, a midsole, an outsole, a unisole, an insole and a full shoe: an integrated sandal, a flip-flop and a full foam shoe.
[0114] Methods and uses
[0115] The present invention also relates to a method for manufacturing an article, the method comprising:
[0116] (A) mixing a foam composition, wherein the foam composition comprises:
[0117] a) a resin composition comprising:
[0118] a1) 25 to 100 phr of a copolymer of ethylene and an alkyl (meth)acrylate, wherein the alkyl (meth)acrylate is selected from methyl (meth)acrylate and butyl (meth)acrylate; and
[0119] a2) 0 to 75 phr of copolymers of ethylene and vinyl acetate;
[0120] (b) 1 phr to 25 phr of a foam composition additive;
[0121] (B) molding (preferably injection molding) and curing the foam material in a mold; and
[0122] (C) removing the foamed material from the mold and producing an article comprising or consisting of the foamed material.
[0123] The resin composition of the foam material and the foam composition additives may be selected from the above-mentioned embodiments.
[0124] The mixing step (A) is preferably performed at a temperature ranging from 80°C to 150°C. The molding step (B) is preferably performed at a temperature ranging from 120°C to 200°C.
[0125] The features of steps (A) and (B) of the process for preparing the foam material are as described above and these features are characteristic of the present process.
[0126] In step (C) of the present method, the foam material is removed from the mold and used directly as the intended product, or it can be further processed into a product comprising the foam material. For example, the product can be a full foam shoe, or it can be a sole of a shoe.
[0127] The method may further comprise a step of stabilizing the foam material. Preferably, the foam material is stabilized in a stabilization tunnel under infrared light irradiation (typically in the wavelength range of 700 nm to 1 mm), preferably at between 80° C. and 50° C. for 30 to 40 minutes. This step may be performed before or after the foam material is removed from the mold, preferably it is performed after the foam material is removed from the mold.
[0128] In a specific embodiment, the article is an article of footwear.
[0129] The present invention also relates to the use of a foam material according to any of the above embodiments in an article for improving the stability of the article to temperature changes, preferably measured by storage modulus at different temperatures. The article is preferably a footwear article as described above.
[0130] Example
[0131] Test Method
[0132] The following measurement methods apply to the description and experimental parts of this application.
[0133] Melt flow rate (MFR)
[0134] Melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The higher the melt flow rate, the lower the viscosity of the polymer. At 190°C, at 2.16 kg (MFR2) or 21.6 kg (MFR 21 ) is measured under a load of .
[0135] Polymer density
[0136] The density of the polymer is measured according to ISO 1183-1:2004 (method A) on compression moulded test specimens prepared according to EN ISO 1872-2 (February 2007) and is expressed in kg / m 3 Given.
[0137] Comonomer content
[0138] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the comonomer content of the polymers.
[0139] Quantitative data were recorded in the melt using a Bruker Avance III 500 NMR spectrometer operating at 500.13 MHz. 1 H NMR spectroscopy. Nitrogen was used for all pneumatics and the temperature was 150 °C. 13 All spectra were recorded using a C-optimized 7 mm magic angle spinning (MAS) probe. Approximately 200 mg of material was loaded into a 7 mm outer diameter zirconium oxide MAS rotor and spun at 4 kHz. This setup was chosen primarily for the high sensitivity required for rapid identification and precise quantification {Klimke06, Parkinson07, Castignolles09}. Standard single pulse excitation was employed with a 2 s recycle delay {Pollard04, Klimke06}. A total of 64 transients were acquired for each spectrum.
[0140] A custom-made automated spectroscopic analysis program was used to quantify 1 H NMR spectra were processed, integrated and quantitatively determined. All chemical shifts were internally referenced to the bulk vinyl methylene signal at 1.33 ppm.
[0141] The determination of the VA, BA and MA contents is described in detail below. The determination of the contents of the corresponding methylated compounds BMA and MMA can be carried out in an analogous manner by taking into account the corresponding molecular weights.
[0142] Attributable to the incorporation of butyl acrylate (BA) {Brandolini01}:
[0143]
[0144] The integration of the signal at 4.1 ppm assigned to the 4BA site was used to quantify the incorporation of butyl acrylate (BA), calculating the number of reported nuclei for each comonomer in the different sequences:
[0145] BA=I 4BA / 2
[0146] Use between 0.00-3.00 ppm of the main aliphatic (I 主体 The ethylene content is quantified by integrating the 1BA(3), 2BA(2), 3BA(2), BA(1) and αBA(2) signals from isolated butyl acrylate incorporation, as well as sites from polyethylene sequences. The total ethylene content is calculated based on the bulk integral, compensating for the BA sites mentioned above:
[0147] E=(1 / 4)*[I 主体 -10*BA]
[0148] The total mole fraction of butyl acrylate (BA) in the polymer is calculated as:
[0149] fBA=BA / (E+BA)
[0150] The total comonomer incorporation (mole percent) of butyl acrylate (BA) was calculated from the mole fractions in the standard manner:
[0151] BA[mol%]=100*fBA
[0152] The total monomer incorporation (weight percent) of butyl acrylate (BA) was calculated in the standard manner from the mole fraction and molecular weight of the monomers:
[0153] BA[wt%]=100*(fBA*128.17) / ((fBA*128.17)+((1-fBA)*28.05))
[0154] Attributable to the incorporation of methyl acrylate (MA) {Brandolini01}:
[0155]
[0156] The total incorporation of methyl acrylate was quantified using the integral of the signal attributed to the 1MA site at 3.6 ppm, calculating the number of reporter nuclei for each comonomer in the different sequences:
[0157] MA=I 1MA / 3
[0158] Use between 0.00-3.00 ppm of the main aliphatic (I 主体 The ethylene content is quantified by integrating the ) signal. The total ethylene content is calculated based on the bulk integral and compensated for the observed comonomer:
[0159] E=(1 / 4)*[I 主体 -3*MA]
[0160] The total mole fraction of methyl acrylate in the polymer is calculated as:
[0161] fMA=MA / (E+MA)
[0162] The total comonomer incorporation (mole percent) of methyl acrylate was calculated from the mole fractions in the standard manner:
[0163] MA [mol%] = 100 * fMA
[0164] The total monomer incorporation of methyl acrylate (weight percent) was calculated from the mole fractions in the standard manner:
[0165] MA[wt%]=100*(fMA*86.09) / ((fMA*86.09)+((1-fMA)*28.05))
[0166] Attributable to the incorporation of vinyl acetate (VA) {Brandolini01}:
[0167]
[0168] The incorporation of vinyl acetate (VA) was quantified using the integral of the signal assigned to the *VA site at 4.9 ppm, calculating the number of reported nuclei for each comonomer in the different sequences:
[0169] VA=I *VA
[0170] Use between 0.00-3.00 ppm of the main aliphatic (I 主体 ) signal to quantify the ethylene content. This integral includes the 1VA (3 protons) and αVA (2 protons) sites, as well as sites from the polyethylene sequence. The total ethylene content is calculated based on the bulk integral, compensating for the VA sites mentioned above:
[0171] E=(1 / 4)*[I 主体 -5*VA]
[0172] The total mole fraction of vinyl acetate (VA) in the polymer is calculated as:
[0173] fVA=VA / (E+VA)
[0174] The total comonomer incorporation (mole percent) of vinyl acetate (VA) was calculated in the standard manner from the mole fractions:
[0175] VA[mol%]=100*fVA
[0176] The total comonomer incorporation (weight percent) of vinyl acetate (VA) is calculated in the standard manner from the mole fraction and molecular weight of the monomers:
[0177] VA[wt%] = 100*(fVA*86.09) / ((fVA*86.09)+((1 - fVA)*28.05))
[0178] References:
[0179] Brandolini01: A.J. Brandolini, D.D. Hills, “NMR spectra of polymers and polymer additives”, Marcel Deker Inc., 2000;
[0180] Pollard04: Pollard, M., Klimke, K., Graf, R., Spiess, H.W., Wilhelm, M., Sperber, O., Piel, C., Kaminsky, W., Macromolecules 2004; 37:813;
[0181] Klimke06: Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, H.W., Wilhelm, M., Macromol. Chem. Phys. 2006; 207:382;
[0182] Parkinson07: Parkinson, M., Klimke, K., Spiess, H.W., Wilhelm, M., Macromol. Chem. Phys. 2007; 208:2128;
[0183] Castignolles09: Castignolles, P., Graf, R., Parkinson, M., Wilhelm, M., Gaborieau, M., Polymer 50(2009)2373.
[0184] XHU fraction
[0185] The xylene heat insolubles (XHU) are analyzed according to ISO 10147. Therefore, 1 g of sample is weighed to the nearest 0.1 mg (m1) and placed in a stainless steel mesh bag made of the following material ("stainless steel quality 1.4401"). The bag with the polymer sample is weighed to the nearest 0.1 mg (m2) and placed in a round flask with 700 mL of xylene (o-xylene or p-xylene, chromatographic purity > 98%). The xylene is kept under reflux conditions for 5 h. The bag containing the insolubles is removed from the flask and the polymer solution residue is washed with a fresh portion of 700 mL of xylene under reflux conditions for 30 minutes. The bag is then removed from the flask and dried in vacuo at 90°C to constant weight. After cooling to room temperature in a desiccator, the bag is weighed to the nearest 0.1 mg (m3).
[0186]
[0187] XHU = xylene heat-insoluble matter amount
[0188] m1 = sample weight, in g
[0189] m2 = weight of the bag containing the sample, in grams
[0190] m3 = weight of the bag containing the insoluble residue, in grams
[0191] The xylene heat soluble fraction was obtained by evaporating xylene from the xylene solution. This fraction was dried overnight under vacuum at 60°C before further analysis by other analytical tests such as NMR spectroscopy.
[0192] Melting and crystallization temperature
[0193] A TA Instruments Q2000 differential scanning calorimeter calibrated with indium, zinc and tin was used and operated at a nitrogen flow rate of 50 mL / min. The thermal program employed consisted of a first heating step from 0°C to 180°C to eliminate the previous thermal history, and a cooling step at a rate of 10°C / min. The melting behavior was obtained by performing a second heating scan from 0°C to 180°C at a rate of 10°C / min. The crystallization and melting temperatures were taken from the peaks of the cooling scan and the second heating scan, respectively. The DSC curve was integrated from 30°C to the end of the melting peak to evaluate the melting enthalpy.
[0194] Rheological measurements
[0195] a) Dynamic shear measurement (frequency sweep measurement)
[0196] As described above or below, the characterization of the polymer composition or the melt of the polymer by dynamic shear measurement complies with ISO standards 6721-1 and 6721-10. The measurement is carried out on an Anton Paar MCR501 stress-controlled rotational rheometer equipped with a 25 mm parallel plate geometry. The measurement is carried out on compression molded plates, using a nitrogen atmosphere and setting the strain in the linear viscoelastic range. The oscillatory shear test is carried out at 190° C., applying a frequency range of 0.01 rad / s to 600 rad / s, and setting a gap of 1.3 mm.
[0197] In a dynamic shear test, the probe is subjected to uniform deformation under sinusoidally varying shear strain or shear stress (strain and stress controlled modes, respectively). In a controlled strain test, the sinusoidal strain to which the probe is subjected can be expressed as
[0198] γ(t)=γ0 sin(ωt) (1)
[0199] If the applied strain is within the linear viscoelastic range, the resulting sinusoidal stress response can be expressed as
[0200] σ(t) = σ0 sin(ωt + δ) (2)
[0201] Where σ0 and γ0 are stress and strain amplitudes, respectively.
[0202] ω is the angular frequency
[0203] δ is the phase shift (loss angle between applied strain and stress response)
[0204] t is time
[0205] Dynamic test results are usually expressed in terms of several different rheological functions, namely the shear storage modulus G', the shear loss modulus G", the complex shear modulus G*, the complex shear viscosity η*, the dynamic shear viscosity η', the heterogeneous component of the complex shear viscosity η", and the loss tangent tanδ, which can be expressed as:
[0206]
[0207] G* = G' + iG” [Pa] (5)
[0208] η* = η' - iη” [Pa.s] (6)
[0209]
[0210] The values of storage modulus (G'), loss modulus (G"), complex modulus (G*), and complex viscosity (η*) were obtained as a function of frequency (ω).
[0211] So, for example, η* 300rad / s (eta* 300rad / s or eta 300 ) is used as an abbreviation for the complex viscosity at a frequency of 300 rad / s, η* 0.05rad / s (eta* 0.05rad / s or eta 0.05 ) is used as an abbreviation for the complex viscosity at a frequency of 0.05 rad / s.
[0212] The polydispersity index PI is defined by Equation 10.
[0213]
[0214] where ω COP is the crossover angular frequency, which refers to the angular frequency when the storage modulus G' is equal to the loss modulus G".
[0215] These values were determined by means of a single-point interpolation procedure defined in the Rheoplus software. In cases where a given G* value was not reached experimentally, it was determined by extrapolation using the same procedure as before. In both cases (interpolation or extrapolation), the options in Rheoplus "-Interpolate y values to x values from parameters" and "Logarithmic interpolation type" were applied.
[0216] References :
[0217] [1]Rheological characterization of polyethylene fractions” Heino, EL, Lehtinen, A., Tanner J., J., Neste Oy, Porvoo, Finland, Theor.Appl.Rheol., Proc.Int.Congr.Rheol, 11th (1992), 1, 360-362.
[0218] [2]The influence of molecular structure on some rheologicalproperties of polyethylene", Heino, EL, Borealis Polymers Oy, Porvoo, Finland, Annual Transactions of the Nordic Rheology Society, 1995.).
[0219] [3]Definition of terms relating to the non-ultimate mechanicalproperties of polymers,Pure&Appl.Chem.,Vol.70,No.3,pp.701-754,1998.
[0220] b) Large Amplitude Oscillatory Shear (LAOS)
[0221] The nonlinear viscoelastic behavior under shear flow has been investigated using the large amplitude oscillatory shear method. This method requires the application of a sinusoidal strain amplitude γ0 at a given angular frequency ω for a given time t. As long as the applied sinusoidal strain is high enough, a nonlinear response will occur. In this case, the stress σ is a function of the applied strain amplitude, time, and angular frequency. Under these conditions, the nonlinear stress response is still a periodic function; however, it can no longer be represented by a single harmonic sine wave. The stress resulting from the nonlinear viscoelastic response [1-3] can be represented by a Fourier series that includes contributions from higher-order harmonics:
[0222] σ(t,ω,γ0)=γ0·Σ n [G' n (ω,γ0)·sin(nωt)+G” n (ω,γ0)·cos(nωt)]
[0223] Where σ = stress response
[0224] t = time
[0225] ω=frequency
[0226] γ0=strain amplitude
[0227] n = number of harmonics
[0228] G” n = nth order elastic Fourier coefficient
[0229] G” n = nth order elastic Fourier coefficient
[0230] Large Amplitude Oscillatory Shear (LAOS) was used to analyze the nonlinear viscoelastic response. Time scan measurements were performed on an RPA2000 rheometer from Alpha Technologies in conjunction with a standard double cone die. During the measurement, the test chamber was sealed and a pressure of approximately 6 MPa was applied. The LAOS test was performed at an applied temperature of 190°C, an angular frequency of 0.628 rad / s, and 1000% (LAOS NLFThe nonlinear response was determined only after at least 20 cycles of each measurement to ensure that steady-state conditions were reached. The large amplitude oscillatory shear nonlinearity coefficient (LAOS) NLF ) is defined as:
[0231]
[0232] Where G'1 = first order elastic Fourier coefficient
[0233] G'3 = third-order elastic Fourier coefficient
[0234] References :
[0235] [1] JMDealy, KFWissbrun, Melt Rheology and Its Role in Plastics Processing: Theory and Applications; edited by Van Nostrand Reinhold, New York (1990).
[0236] [2]S.Filipe,Non-Linear Rheology of Polymer Melts,AIP ConferenceProceedings 1152,pp.168-174(2009)3.
[0237] [3] M. Wilhelm, Macromol. Mat. Eng. 287, 83-105 (2002).
[0238] [4]S.Filipe,K.Hofstadler,K.Klimke,ATTran,Non-Linear RheologicalParameters for Characterization of Molecular Structural Properties inPolyolefins,Proceedings of Annual European Rheology Conference,135(2010).
[0239] [5] S. Filipe, K. Klimke, ATTran, J. Reussner, Proceedings of Novel Non-Linear Rheological Parameters for Molecular Structural Characterization of Polyolefins, Novel Trends in Rheology IV, Zlin, Check Republik (2011).
[0240] [6] K.Klimke, S.Filipe, ATTran, Non-linear rheological parameters for characterization of molecular structural properties in polyolefins, Proceedings of European Polymer Conference, Granada, Spain (2011).
[0241] Stability to temperature changes (DMTA): Measurement of foams
[0242] The stability to temperature changes was determined by dynamic mechanical thermal analysis (DMTA). Cylindrical foam samples with a height of 10 mm and a diameter of 20 mm were used. They were tested in a temperature scanning mode from -30°C to 80°C with a fixed stress of 0.270 MPa, a frequency of 3 Hz, and a heating rate of 2°C / min. Before starting the test, the samples were stabilized at -30°C for 8 min. The equipment used for DMTA was Metravib DMA +300 or +1000. According to the storage modulus (in MPa) E' measured at -20°C -20 and the storage modulus E' measured at 23 °C 23 Calculate the ratio.
[0243] Stability to temperature changes (DMTA): Measurement of particles
[0244] In dynamic mechanical thermal analysis in tension mode, the sample is subjected to a constant load and an applied sinusoidal tensile strain. At sufficiently low deformations, the material response remains in the linear viscoelastic region independent of the strain amplitude.
[0245] The tensile storage modulus E'(1) and the tensile loss modulus E"(2) are determined by the following equations:
[0246]
[0247] in
[0248] ΔF A is the measured amplitude of the dynamic force in Newtons
[0249] S A is the measured amplitude of the dynamic displacement in meters
[0250] L a is the distance between the fixtures, in meters
[0251] b is the width of the sample, in meters
[0252] d is the thickness of the sample, in meters
[0253] δ is the measured phase angle in degrees
[0254] The so-called damping coefficient is determined as described in the following equation.
[0255]
[0256] The characterization of dynamic mechanical properties complies with ISO standards 6721-1, 6721-4, 6721-11. The measurements were performed on a "Netzsch DMA242E Artemis" strain / stress controlled dynamic mechanical analyzer equipped with a tensile sample holder for rectangular specimen geometries. Rectangular specimens cut from compression molded plaques produced using a "Collin 400P / M" hot press were measured, melted at 200 °C and an annealing time of 300 seconds at a pressure of 5 bar, then cooled to room temperature using a compression pressure of 25 bar for 300 seconds and a cooling rate of 15 K / min using a pressure of 50 bar. Compression molded plaques with a geometry of 100 × 100 × 1 mm were prepared and had a minimum rest time of at least 96 hours after compression molding. Rectangular specimens prepared using a laboratory cutter to ensure a geometry of length × width × thickness of 20 mm × 2 mm × 1 mm were used to clamp the specimens. At room temperature, the free tensile length measured with a caliper with an accuracy of 0.05 mm is about 10 mm. The width and thickness are measured using a suitable length gauge with an accuracy of 0001 mm. Dynamic mechanical thermal analysis was carried out in an inert atmosphere, with liquid nitrogen cooling, in the temperature range from -170°C to +90°C, with a heating rate of 2 K / min, a frequency of 1 Hz, in strain-stress control mode, with a maximum dynamic applied stress of 1.70 MPa, a static load of 0.20 MPa and a maximum strain of 0.20%. To avoid deformation, the specimens were clamped with a screw torque of 2.5 cNm in the temperature range of -100°C to -130°C. Conditioning was carried out at a starting temperature of -170°C, with an isothermal period of 30 minutes, of which the last 5 minutes had an E' change equal to or less than 5 MPa per minute. According to the storage modulus E' measured at -20°C -20 and the storage modulus E' measured at 23 °C 23 Calculate the ratio.
[0257] References :
[0258] [1] "Dynamic mechanical analysis: a practical introduction" Kevin P. Menard 2008by Taylor&Francis Group,LLC,Dynamic Testing andInstrumentation,71-76,2008
[0259] Foam density
[0260] The foam density of the foam material (measured in SGS laboratory) was determined according to SATRA test method TM134:1998 at 23±2°C and 50±5% RH.
[0261] The foam density of the foam material is determined according to the "Archimedes" principle, which measures the weight of a sample in two media of different densities (water and air). The test sample is first weighed in air. It is then completely immersed in water and weighed again. The apparent weight loss is equal to the weight of the water displaced. The volume displacement is then calculated, which is equal to the volume of the test piece and divided by the weight in air to give the density.
[0262] Prior to measurement, the test samples and water were conditioned at ambient conditions (23 ± 2 °C) for 3 hours.
[0263] Volume loss due to wear
[0264] The volume loss of the foam due to abrasion (measured in SGS laboratories) was determined according to SATRA test method TM174:1994 (non-rotating) at 23±2°C and 50±5% RH.
[0265] Five days after the preparation of the foam, three test specimens with a diameter of 16 mm were cut from the foam with a thickness of 10 mm. The specimens were conditioned under ambient conditions (23±2° C. and 50±5% RH) for 3 hours.
[0266] The test was carried out on a Cotech wear tester (rotating drum type) with the following settings: force: 10 ± 0.2 N; carriage speed: 4.2 ± 0.04 mm / drum rotation; drum speed: 40 ± 1 rpm; and the following adjustments and conditions: the sample protrudes 2.0 ± 0.2 mm from the opening; the cylinder rotates 84 times (relative to 40 m) under vacuum conditions.
[0267] First measure a standard rubber sample (same size as the test sample). Remove the sample from the machine and weigh it to obtain the value [M0]. Repeat the measurement with the same sample and weigh it to obtain the value [M1].
[0268] The mass loss is calculated as follows: [ML] = [M1] - [M0]. Only the measured values for [ML] in the range of 180 to 220 mg are considered and recorded as [C1] values. Repeat the measurement with the test sample in a similar manner to determine the mass loss [T1]. Repeat the measurement with 2 standard rubber samples and 2 test samples to obtain [C2], [C3], [T2] and [T3].
[0269] The volume loss is determined by: (400 x [Tn]) / {[D] x ([Cn] + [Cn + 1])}, wherein the average of three volume loss values is used. D represents the density of the test sample determined according to SATRA TM134.
[0270] Shrinkage
[0271] The shrinkage of the foam material (measured in SGS laboratories) was determined according to SATRA test method TM70:2001, after exposure to 70°C for 24 hours.
[0272] Two test specimens of 150 mm x 25 mm were cut from the foam material having a thickness of 10 mm, with one specimen cut in the machine injection direction and the other cut in the transverse direction. The specimens were conditioned at ambient conditions (23±2° C. and 50±5% RH) for 24 hours.
[0273] Two shallow cuts of 0.5 mm were made on each sample at (approximately) 100 mm intervals, and the distance between the cuts was measured and recorded as [D1] and [D2] (for both samples). The samples were heated in an oven at 70±1°C for 24 hours, removed from the oven, and cooled at ambient conditions for 30 minutes. The distance between the cuts was measured again and recorded as [F1] and [F2] (for both samples). The shrinkage percentages [P1] and [P2] were determined as [P1] = {([F1] - [D1]) * 100} / [D1] and [P2] = {([F2] - [D2]) * 100} / [D2], and the average was taken from these values to obtain the final shrinkage percentage.
[0274] Foam hardness
[0275] Foam hardness (measured in SGS laboratory) was determined according to test method SATRATM 205 at 23±2°C and 50±5% RH.
[0276] Tear strength
[0277] The tear strength in the machine direction (measured in SGS laboratory) was determined according to ISO 34-1:2015 at 23±2°C and 50±5% RH and a speed of 100 mm / min.
[0278] Deceleration / peak force
[0279] The deceleration and peak force are determined as follows:
[0280] The Dynatup impactor (or vertical drop hammer) is equipped with two force sensors: one at the impactor level and one at the base level (where the foam is placed). Each force sensor samples at 10KHz and starts recording when the tip of the impactor is 1cm from the foam surface (there is a beam sensor (Beam Photoelectric Sensor) that needs to be manually adjusted depending on the thickness of the foam). The impactor is spherical with a radius of 65mm.
[0281] Thus, a time / force curve is obtained which starts from the moment before the impact and covers the entire time of the impact process and the two or three subsequent rebounds. The data used are those of the sensor installed at the impactor level. The force peak corresponds to the maximum force recorded during the first impact.
[0282] At the same time as the force peak was measured, the deceleration was measured on the same machine. Position data provided by a Codamotion motion analysis system (Coda CX1, Charnwood Dynamics Ltd) was used. The position data was sampled at 800 Hz. The system was calibrated so that there was motion only in the vertical axis. The position data was differentiated twice to obtain the acceleration curve (position -> velocity -> acceleration). The deceleration peak corresponds to the maximum acceleration obtained during the first impact. The deceleration was initially measured in mm / s 2 Calculate in units and then convert to m / s 2 and G.
[0283] experiment
[0284] Production of EVA, EMA and EBA copolymers
[0285] The production methods of EVA, EMA and EBA copolymers are described below. Similar methods can be used to produce EMMA and EBMA copolymers containing the corresponding methylated compounds.
[0286] EVA
[0287] Fresh and recycled ethylene, comonomers and optional chain transfer agents are compressed to the desired reactor pressure (typically between 1000 and 2000 bar (100 MPa and 200 MPa)). The temperature of the compressed stream is adjusted to achieve the desired reactor inlet conditions (typically between 150°C and 280°C). The polymerization is initiated and maintained by injecting a commercially available peroxide free radical initiator dissolved in a substantially inert hydrocarbon solvent at one or more points in the reactor. The flow rates of comonomer, initiator and optional chain transfer agent are adjusted to achieve the desired polymer properties, such as comonomer content and MFR. The reaction mixture is depressurized by a pressure control valve, cooled, and the polymer is separated from the unreacted gases.
[0288] EMA
[0289] Fresh and recycled ethylene and comonomer methyl acrylate were compressed to an initial reactor pressure of 2650 bar (265 MPa) and divided into two parallel streams to feed the front and side ends of the batch feed 2 zone reactor, the L / D of which varied between 17300 and 30400. The comonomer addition reached 24 wt.% in the final polymer by feeding the compressor stream in a 1:1 ratio (front:side). The MFR2 of the final polymer was maintained at 2 g / 10 min. After compression, the front stream was heated to 160°C in a preheating section before entering the front end region of the reactor, and the side stream was cooled and entered from the side of the reactor. After the preheating section and at one or more locations along the reactor, a mixture of commercially available peroxide free radical initiators dissolved in a substantially inert hydrocarbon solvent was injected in an amount sufficient to achieve an exothermic polymerization reaction reaching peak temperatures of 270°C and 270°C, respectively (with cooling to 170°C). The reaction mixture is decompressed and cooled through a pressure control valve to separate the polymer from the unreacted gas.
[0290] EBA
[0291] Fresh and recycled ethylene and comonomer butyl acrylate were compressed to an initial reactor pressure of 2550 bar (255 MPa) and divided into two parallel streams to feed the front and side ends of the batch feed 2 zone reactor, the L / D of which varied between 17300 and 30400. The comonomer addition reached 23 wt.% in the final polymer by feeding the compressor stream in a 1:1 ratio (front:side). The MFR2 of the final polymer was maintained at 4 g / 10 min. After compression, the front stream was heated to 160°C in a preheating section before entering the front end of the reactor, and the side stream was cooled and entered from the side of the reactor. After the preheating section and at one or more locations along the reactor, a mixture of commercial peroxide free radical initiators dissolved in a substantially inert hydrocarbon solvent was injected in an amount sufficient to achieve an exothermic polymerization reaction reaching peak temperatures of 285°C and 285°C, respectively (cooling to 165°C during the reaction). The reaction mixture is decompressed and cooled through a pressure control valve to separate the polymer from the unreacted gas.
[0292] Foam
[0293] Foam materials were produced from foam compositions containing single EMA, EBA or EVA copolymers as well as from dry blends of EVA / EMA and EVA / EBA copolymers. The properties of the single copolymers (before foaming) are summarized in Table 1 below.
[0294] Table 1: Properties of EMA, EBA and EVA copolymers.
[0295]
[0296]
[0297] Foam compositions containing the EMA copolymer or the EBA copolymer and optionally the EVA copolymer were prepared and were compositions according to the invention (IE1 to IE10). Comparative compositions contained only EVA copolymers (CE1 and CE2). Table 2 shows the contents of the foam compositions.
[0298] Table 2: Contents of foam compositions.
[0299]
[0300] AC3000=azodicarbonamide (foaming agent)
[0301] BIBP = 1,3-bis(tert-butylperoxyisopropyl)benzene (crosslinking agent)
[0302] ZnO (foaming agent activator)
[0303] Additives = mixture of fillers, pigments and other additives
[0304] The compositions were mixed and extruded according to the above method and the properties of the foams (after foaming and crosslinking) were determined. These properties are summarized in Tables 3 and 4.
[0305] Table 3: Properties of foam materials (1).
[0306]
[0307]
[0308] Table 4: Properties of foam materials (2).
[0309]
[0310] These examples show that lower levels of blowing agent (AC3000) are required in the inventive examples to achieve a given (lower) foam density than in the comparative examples. This is particularly evident when 2 phr of AC3000 is used, and the inventive examples (except IE6) achieve lower foam densities than comparative example CE1. Even when 2.5 phr of AC3000 is used in comparative example CE2, its density is higher than several inventive examples at 2 phr of AC3000.
[0311] All the inventive examples show a better stability to temperature variations than the comparative examples, as assessed by the ratio of the tensile modulus E' at -20°C and 23°C by the DMTA method.
[0312] All inventive examples achieved lower decelerations than the comparative examples. At the same or lower AC3000 dosage, the force peaks were also lower.
Claims
1. A foam composition comprising: a) a resin composition comprising: a1) 25 to 100 phr of a copolymer of ethylene and an alkyl (meth)acrylate, wherein the alkyl (meth)acrylate is selected from methyl (meth)acrylate and butyl (meth)acrylate; and a2) 0 to 75 phr of a copolymer of ethylene and vinyl acetate; and b) 1 to 25 phr of foam composition additives.
2. The foam composition according to claim 1, wherein the foam composition comprises one or more of the additives b1) to b4): b1) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a chemical blowing agent; b2) 0.1 to 3 phr, preferably 0.1 to 1.5 phr, of a crosslinking agent; b3) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a blowing agent activator; and b4) 0 to 20 phr, preferably 0 to 15 phr, of other foam composition additives.
3. A foam composition according to any one of the preceding claims, consisting of: a) a resin composition comprising: a1) 25 to 100 phr of a copolymer of ethylene and an alkyl (meth)acrylate, wherein the alkyl (meth)acrylate is selected from methyl (meth)acrylate and butyl (meth)acrylate; and a2) 0 to 75 phr of copolymers of ethylene and vinyl acetate; and b1) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a chemical blowing agent; b2) 0.1 to 3 phr, preferably 0.1 to 1.5 phr, of a crosslinking agent; b3) 0.1 to 10 phr, preferably 0.1 to 3 phr, of a blowing agent activator; and b4) 0 to 20 phr, preferably 0 to 15 phr, of other foam composition additives.
4. The foam composition according to any one of the preceding claims, wherein the resin composition comprises: a1) 25 to 75 phr of a copolymer of ethylene and an alkyl (meth)acrylate, wherein the alkyl (meth)acrylate is selected from methyl (meth)acrylate and butyl (meth)acrylate; and a2) 25 to 75 phr of a copolymer of ethylene and vinyl acetate.
5. Foam composition according to any of the preceding claims, wherein the copolymer of ethylene and alkyl (meth)acrylate is a copolymer of ethylene and butyl (meth)acrylate, preferably a copolymer of ethylene and butyl (meth)acrylate having an MFR2 determined according to ISO 1133 in the range of 2.0 to 5.0 (g / 10 min, 190°C), preferably in the range of 3.0 to 4.0 (g / 10 min, 190°C).
6. Foam composition according to any one of claims 1 to 4, wherein the copolymer of ethylene and an alkyl (meth)acrylate is a copolymer of ethylene and methyl (meth)acrylate, preferably a copolymer of ethylene and methyl (meth)acrylate having an MFR2 determined according to ISO 1133 in the range of 1.0 to 4.0 (g / 10min, 190°C), preferably in the range of 1.5 to 2.5 (g / 10min, 190°C).
7. The foam composition according to any one of the preceding claims, comprising from 0.1 to 3 phr of a blowing agent.
8. A foam composition according to any one of the preceding claims, wherein: The content of the alkyl (meth)acrylate comonomer incorporated into the copolymer of ethylene and alkyl (meth)acrylate is 15 to 35 wt.% based on the total weight of the copolymer of ethylene and alkyl (meth)acrylate as determined by NMR spectroscopy.
9. A foam material obtained from a foam composition according to any one of the preceding claims.
10. The foam material of claim 9, wherein the foam material is characterized by at least one of the following features: c1) Storage modulus E' measured at -20°C -20 Storage modulus E' measured at 23 °C 23 The ratio of is less than 65, wherein the storage modulus is determined by dynamic mechanical thermal analysis (DMTA) as described in the specification; c2) Volume loss due to wear is less than 1500mm 3 , wherein the volume loss by abrasion is determined as described in the specification; and c3) a shrinkage of less than 5%, wherein the shrinkage is determined as described in the description.
11. The foam material according to any one of claims 9 and 10, having a relative humidity of 0.16 g / cm 3 Up to 0.28g / cm 3 The density is within the range of 0.20 g / cm 3 Up to 0.28g / cm 3 Density within the range is determined as described in the instructions.
12. An article of footwear comprising or consisting of a foam material according to any one of claims 9 to 11.
13. A method for manufacturing an article, the method comprising: (A) mixing a foam composition, wherein the foam composition comprises: (a) a resin composition comprising: a1) 25 to 100 phr of a copolymer of ethylene and an alkyl (meth)acrylate, wherein the alkyl (meth)acrylate is selected from methyl (meth)acrylate and butyl (meth)acrylate; and a2) 0 to 75 phr of copolymers of ethylene and vinyl acetate; (b) 1 phr to 25 phr of a foam composition additive; (B) molding and curing the foam material in a mold; and (C) removing the foamed material from the mold and producing an article comprising or consisting of the foamed material.
14. The method of claim 13, wherein the article is an article of footwear.
15. Use of the foam material according to any one of claims 9 to 11 in an article for increasing the stability of the article to temperature changes, wherein the article is preferably a footwear article.
Citation Information
Patent Citations
Foam compositions and uses thereof
US20190276650A1